Implementasi Cloning Data Menggunakan Aplikasi EaseUS Partition Master Dengan Menerapkan Metode Workflow - Yennimar -; Julfan Farman Zebua; Wikesyah Putri Sitorus; Kristina Ginting; Yans Y.M.P. Situmorang (JURNAL TEKNOLOGI DAN ILMU KOMPUTER PRIMA (JUTIKOMP), 2023)
Data cloning implementation is an essential process in information technology to duplicate content from one storage device to another. EaseUS Partition Master is a popular software used to implement this data cloning process. This abstract discusses the implementation of data cloning using EaseUS Partition Master. Data cloning is an efficient way to duplicate the entire contents of one hard drive or partition to another storage device. EaseUS Partition Master offers extensive capabilities in performing data cloning with various features that can facilitate users in carrying out the process. One of the most commonly used cloning features is "Disk Clone," which allows users to duplicate an entire hard drive to another hard drive. In this case, EaseUS Partition Master will automatically detect all existing partitions, and users can select the partitions they want to clone. In addition, EaseUS Partition Master also provides a "Partition Clone" feature, which allows users to clone a specific partition from one hard drive to another. This feature is helpful if users only want to duplicate data from a few selected partitions. Once the user has selected the desired type of cloning, EaseUS Partition Master will guide the user through the following steps. This includes selecting a target hard drive or partition to place the cloned data on and customizing the cloning settings according to the user's needs. During the cloning process, EaseUS Partition Master provides a clear and informative view of the cloning progress. Users can track and monitor the process to ensure everything is going well. Overall, implementing data cloning using EaseUS Partition Master provides a reliable and easy-to-use solution for users who need an efficient cloning process. With its comprehensive features and intuitive interface, the software allows users to clone their data without any significant difficulties.